Pengaruh Disiplin kerja dan Lingkungan Kerja Fisik terhadap Kinerja Karyawan pada CV Anugerah Mulya Rejeki - Krisnawan, Wahyu; Santoso, Bowo (Jurnal Ekonomi, Bisnis dan Manajemen, 2026)
This study aims to determine the effect of work discipline and the physical work environment on employee performance at CV. Anugerah Mulya Rejeki. This topic is important in the field of human resource management because work discipline and the physical work environment are key factors influencing employee performance, particularly in the increasingly competitive plastic industry. This research was conducted to provide a deeper understanding of how work discipline and the physical work environment can be utilized by companies to improve performance and ensure business sustainability. This study employs a quantitative approach using SPSS with multiple linear regression analysis. The sample consists of 34 respondents selected using a saturated sampling technique. Data were collected through questionnaires distributed to employees of CV. Anugerah Mulya Rejeki. The results show that work discipline has a positive and significant effect on employee performance, while the physical work environment does not have a significant effect on employee performance.